2021
DOI: 10.1111/faf.12621
|View full text |Cite
|
Sign up to set email alerts
|

A unifying hypothesis for the spawning migrations of temperate anguillid eels

Abstract: Anguillid eels grow in freshwater but spawn in the open ocean. The cues that guide eels over long distances to the spawning area are unknown. The Earth's magnetic field can provide directional and positional information and is likely used by catadromous eels during their spawning migration; as magnetosensitivity and compass orientation have been reported in eels. To test whether this is theoretically possible, we compared the migratory routes of five species of temperate eels that undertake long migrations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…Currently, it is not possible to verify whether the Sun culminating to north or south caused the meridional swimming tendencies of eels in this study. Potentially, these meridional swimming tendencies could be due to other orientation clues, such as the geomagnetic field, as discussed for temperate anguillid eels 17 , 45 . Nevertheless, in future studies, it would be worthwhile considering solar cues as a possible candidate factor in the orientation of eels, even when under faint underwater light conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, it is not possible to verify whether the Sun culminating to north or south caused the meridional swimming tendencies of eels in this study. Potentially, these meridional swimming tendencies could be due to other orientation clues, such as the geomagnetic field, as discussed for temperate anguillid eels 17 , 45 . Nevertheless, in future studies, it would be worthwhile considering solar cues as a possible candidate factor in the orientation of eels, even when under faint underwater light conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratory experiments of anguillid eels have shown that magnetic cues may be used by juvenile and adult eels to navigate during migration 41 44 , and this appears to be true for temperate anguillid eels that likely use a magnetic sense for their spawning migrations 45 . Whereas a recent comprehensive review indicated that no single cue or mechanism is used by animals to enable successful navigation over thousands of kilometers 46 .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic field-based migration behavior has been documented in many long-distance migrators such as salmon, eels, sharks, and turtles (Durif et al, 2021;Keller et al, 2021;Lohmann et al, 2007;Putman et al, 2014). In these species, the benefits associated with an ability to use a magnetic compass or map to cross hundreds to thousands of kilometers in pelagic water is clear.…”
Section: Discussionmentioning
confidence: 99%
“…Geomagnetism is considered highly important for navigation of eels during their larval spawning migrations (Durif et al 2021), and hence changes to the Earth's magnetic elds could have negative effects. The Brunhes-Matuyama magnetic reversal occurred ca.…”
Section: Compared To Psmc Analysis (Li and Durbin 2011) Based On Indi...mentioning
confidence: 99%